Optimization of leaching conditions for extraction of magnesium from a chromite beneficiation plant tailing predominantly containing lizardite - Ciftci, Hakan; Arslan, Bekir; Bilen, Aysegul; Arsoy, Zeyni; Ersoy, Bahri (MADEN TETKIK VE ARAMA GENEL MUDURLUGU-MTA, 2021)
In this study, leaching experiments were performed for extraction of magnesium from a chromite beneficiation plant tailing predominantly containing lizardite. The X-ray fluorescence (XRF) and X-ray diffraction (XRD) analyzes showed that the tailing sample contains 39.3wt.% MgO and consist of predominantly lizardite mineral. Hydrochloric acid (HCl) and sulphuric acid (H2SO4) were used as acids separately in leaching experiments. Acid concentration, leaching temperature, leaching time, and solid ratio were investigated as leaching parameters and optimized. Maximum magnesium extraction yield was determined to be nearly 98% for both acids under optimum leaching parameters which leaching temperature was 85 degrees C, solid ratio was 20wt.%, leaching time was 120 minutes, and acid concentrations were 6 M for HCl and 4 M for H2SO4. In addition, it was determined that the leaching residue as a solid state was mainly composed of amorphous silicate according to the XRD analysis. Dissolution rate data were explained using Jander equation. Mg dissolution process found to be diffusion controlled.
Keywords: Leaching; Lizardite; Magnesium; Amorphous silicate; Chromite plant tailing; CARBON CAPTURE; DISSOLUTION KINETICS; SERPENTINE; CHRYSOTILE; STORAGE; SILICA; PH; MINERALIZATION; PRECIPITATION; FIXATION; Geology